Innovative approaches to social geographical research and effective use of economic potential of the Carpathian region - Машіка, Г. В. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2018)
The purpose of this article is to clarify the innovative approaches to social geographical research and effective use of economic potential of the Carpathian region.Methodical base while writing the article was shaped by general scientific methods such as analysis, synthesis, and generalization, deductive and systemic methods.Results. In this article the innovative approaches to social geographical research and effective use of economic potential of the Carpathian region have been revealed. Among the main innovative approaches development of economic potential of the Carpathian region on the basis of energy and resource-saving, as well as development of “green economy” have been suggested. Comparative characteristics of “green economy”, “green growth” and stable development have been brought on. The key principles of “green economy” have been formulated, among which are: harmonization in relations in the system “nature – human – production”; appropriate coherence of economic, social and environmental priorities; protection of both human and nature from the devastating impact of the production activity conducted by society; provision of favorable living conditions in the current and future periods; guaranteeing the growth of the economic potential of society and its socio-cultural development in the conditions of ecological safety. It has also been led upon terms of political provisions in Association Agreement between Ukraine and EU, which foresee establishment of stable economic development and mechanisms of “green” economy in accordance with the principles of strategy realization on stable development; this strategy was initiated at the UN Summit “Rio+20”. The detailed analysis of “green” economy priorities by sectors of economy, such as energy, resourceful, food, social, regional economy, industrial, transport and financial has been carried out. Resource-saving factors of effective use of economic potential of the Carpathian region have been considered, which can be defined as the most popular priorities, leading to the increase in people’s welfare and social justice with significant decrease in ecological risks and ecological deficits. The main directions of rational energy, resource and nature use as well as state strategy in rational nature use have been suggested.Scientific novelty consists in the fact that the prospective ways to improve the market of resource-saving technologies have been suggested, among which are: products and services quality improvement, which are produced by enterprises with adaptation to nature protection requirements, as well as implementation of international standards of resource-saving, development and introduction of new products based on the use of resource-saving technologies, putting into the economy foreign investments on resource-saving production and facilitation of the development of institutions to promote and support resource-saving production.Practical significance consists in the fact that innovative approaches to social geographical research and effective use of economic potential of the Carpathian region, suggested in this article, can be used in practice for efficient exploitation of economic potential of the Carpathian region.